FINANCIAL LITERACY AND DEMOGRAPHIC FACTORS IMPACT ON INVESTMENT TOWARDS UNDERGRADUATE STUDENTS IN BANDUNG - Kristiana (19015044), Nathania
For providing income in the future, assets that is now owned can be invest and sold at a higher price compared with the buying price to obtain greater amount of assets called profit. Unfortunately, the number of investors in Indonesia is still considered low, means the knowledge of managing their financial resources effectively through investment should be increased. Therefore, financial literacy is expected to impact investment. Different previous studies found that financial literacy or demographic factors impact investment. This study combined previous findings and observes how financial literacy and demographic factors could impact undergraduate student to have investment. This research uses quantitative method to collect data using online questionnaire to undergraduate student from 3 selected colleges in Bandung. Methodology that being used are multiple linear regression to know the impact of financial literacy and demographic factors towards investment. The findings show that financial literacy, monthly income, and working income are significantly impact undergraduate studentÃ‚Â’s investment value.